Association between blood urea nitrogen to albumin ratio and diabetic retinopathy: insights from the US National Health and Nutrition Examination Survey - Fei-Fei Dai; Jian-Dong Pan; Xiao-Jie He (International Journal of Ophthalmology)
AIM: To investigate whether blood urea nitrogen to serum albumin ratio (BAR) influences the onset and progression of diabetic retinopathy (DR) in diabetic patients. METHODS: The diabetic individuals were extracted from the National Health and Nutrition Examination Survey (NHANES) database spanning 1999 to 2018. The BAR was calculated as the ratio of blood urea nitrogen to serum albumin. To evaluate the association between BAR levels and DR, a generalized additive model and multivariate logistic regression analysis were performed. Additionally, subgroup analyses were conducted to determine whether other factors modified this association. RESULTS: The number of eligible individuals in the current research endeavor equaled 5798. The resulting data were indicative of the existence of a nearly linearly positive relationship between BAR levels and DR. Following confounding variable adjustment (age, gender, marital status, red blood cell, hemoglobin, lactate dehydrogenase, uric acid, creatinine, gender, red cell distribution width, high-density lipoprotein, glucose, sodium, glycated hemoglobin, hypertension, and total cholesterol), the multivariate investigation implied that an elevated DR risk correlated with elevated levels of BAR (OR: 1.46, 95%CI: 1.20-1.79). This relationship was noted to be reliable and stable across diverse analyses, following the conduction of sensitivity analysis (P for trend: 0.0002). Subgroup analysis showed no statistically significant interactions between BAR and most other risk factors for DR. CONCLUSION: The study provides evidence of a positive association between elevated BAR levels and an increased risk of DR in diabetic individuals.